Asian management of hypertension: Current status, home blood pressure, and specific concerns in Singapore. Issue 3 (31st December 2019) - Tay, Jam Chin; Teo, Boon Wee
Abstract: Despite reductions in hypertension prevalence and improvements in control rates in recent years, almost one‐third of all deaths in Singapore are due to cardiovascular disease and that proportion is growing. Ischemic heart disease is the most common cause of cardiovascular death, ahead of stroke. Local data suggest that awareness and support for home blood pressure monitoring (HBPM) is good, but there are reservations about the accuracy of HBPM devices and physicians cited a lack of time and resources to educate patients about HBPM. In addition, there was a knowledge gap around use of HBPM for evaluating treatment response. This is consistent with the emphasis of using HBPM for the diagnosis, rather than monitoring, of hypertension in the Singapore hypertension guidelines. In the absence of specific HBPM thresholds and targets, it is suggested that HOPE Asia Network consensus documents provide the most locally relevant guidance of the use of HBPM. Calcium channel blockers and angiotensin receptor blockers are the most commonly used antihypertensive agents in Singapore, and monotherapy was relatively uncommon (24%) of patients. Overall, more needs to be done in detecting and managing hypertension in Singapore to address rates of cardiovascular disease and cardiovascular disease mortality. Use of HBPM needs to be encouraged to improve adherence to treatment and optimize BP targets according to Asian perspectives and data.